2021
DOI: 10.3390/atmos12060701
|View full text |Cite
|
Sign up to set email alerts
|

The Superiority of Data-Driven Techniques for Estimation of Daily Pan Evaporation

Abstract: In the present study, estimating pan evaporation (Epan) was evaluated based on different input parameters: maximum and minimum temperatures, relative humidity, wind speed, and bright sunshine hours. The techniques used for estimating Epan were the artificial neural network (ANN), wavelet-based ANN (WANN), radial function-based support vector machine (SVM-RF), linear function-based SVM (SVM-LF), and multi-linear regression (MLR) models. The proposed models were trained and tested in three different scenarios (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 53 publications
3
13
0
Order By: Relevance
“…Throughout the investigation, pan evaporation (EP d ) measurement and predicted values were compared. Statistical assessment was done to compare the accuracy of the applied algorithms (i.e., SVM, RT, REPTree, and RSS) using the root mean square error (RMSE) [8,10,44], mean absolute error (MAE) [7,45], Nash-Sutcliffe efficiency (NSE) [4,45], Willmott index (WI) [8], and correlation coefficient (r) [19]. In addition, qualitative performance was evaluated through graphical scrutiny.…”
Section: Statistical Assessment and Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…Throughout the investigation, pan evaporation (EP d ) measurement and predicted values were compared. Statistical assessment was done to compare the accuracy of the applied algorithms (i.e., SVM, RT, REPTree, and RSS) using the root mean square error (RMSE) [8,10,44], mean absolute error (MAE) [7,45], Nash-Sutcliffe efficiency (NSE) [4,45], Willmott index (WI) [8], and correlation coefficient (r) [19]. In addition, qualitative performance was evaluated through graphical scrutiny.…”
Section: Statistical Assessment and Validationmentioning
confidence: 99%
“…Daily pan evaporation (EP d ) has been extensively used in irrigation scheduling, water balance studies, sustainable water resources management, and hydrological modelling, etc. [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study were compared with the previous studies conducted on modeling pan-evaporation using several artificial intelligence (AI) techniques optimized by bio-inspired algorithms (Kumar et al, 2021;Majhi et al, 2020;Qasem et al, 2019;Salih et al, 2019;Singh et al, 2021). The previous studies reported the effective utility of hybrid AI methods for pan-evaporation at different locations in varying climates through statistical metrics and visual investigation.…”
Section: Discussionmentioning
confidence: 97%